Synergistic effect of KCl, thiourea, GA3 and SA on the germination and early seedling growth enhancement of drought-stressed Malaysian indica rice cv. MR220. (October 2020) - Mahadi, S.N.; Nulit, R.; Mohtar, M.A.; Ibrahim, M.H.; Ab Ghani, N.I.
Abstract: Rice plantation is one of the sectors that severely affected by drought stress worldwide and caused high loss of rice production. Latest, approximately 1164 ha rice plantation was affected due to water scarcity in Malaysia and reduced rice production. This study suggest that treatment by using liquid formulation containing macronutrient and plant growth regulators as one of the strategies to alleviate drought stress in plant growth and development. Hence, this study aimed to assess the synergistic effect of KCl, thiourea (TU), GA3 and SA for the germination and early growth enhancement of drought-stressed rice cv. MR220. MR220 seeds were stressed in -1.2 MPa PEG 6000 solution and germinated in petri dishes containing KCl, TU, GA3 and SA separately for ten days. Results showed that, 1.0 mM of KCl, 2.0 mM of TU, 0.06 mM of GA3 and 1.0 mM of SA were the ideal concentration that enhance the germination and early seedling growth of drought-stressed MR220. Next, the ideal concentrations were combined and the result showed that the best combination treatments for drought-stressed MR220 were 1.0 mM KCl +0.06 mM GA3, 0.06 mM GA3 + 1.0 mM SA and 1.0 mM KCl +2.0 mM TU + 0.06 mM GA3 . These combination treatments significantly increased the germination and seedling growth performance of drought-stressed MR220. The combination treatment of 1.0 mM KCl +2.0 mM TU + 0.06 mM of GA3 showed the most effective in improving germination and seedling growth performance of drought-stressed MR220. Highlights: Drought stress severely affected the germination performance of rice. Liquid enhancer treatment is one of alternative to reduce drought stress in rice germination. Ideal concentration of KCl, thiourea, GA3 and SA able to alleviate drought stress in rice cv. MR220 germination. Synergistic effect of KCl, thiourea, GA3 and SA accelerate the germination performance of drought-stressed MR220 seed.